Essential oil of Artemisia argyi suppresses inflammatory responses by inhibiting JAK/STATs activation. (23rd May 2017) - Chen, Lin-Lin; Zhang, Hao-Jun; Chao, Jung; Liu, Jun-Feng
Abstract: Ethnopharmacological relevance: Artemisia argyi is a herbal medicine traditionally used in Asia for the treatment of bronchitis, dermatitis and arthritis. Recent studies revealed the anti-inflammatory effect of essential oil in this plant. However, the mechanisms underlying the therapeutic potential have not been well elucidated. The present study is aimed to verify its anti-inflammatory effect and investigate the probable mechanisms. Materials and methods: The essential oil from Artemisia argyi (AAEO) was initially tested against LPS-induced production of inflammatory mediators and cytokines in RAW264.7 macrophages. Protein and mRNA expressions of iNOS and COX-2 were determined by Western blotting and RT-PCR analysis, respectively. The effects on the activation of MAPK/NF-κB/AP-1 and JAK/STATs pathway were also investigated by western blot. Meanwhile, in vivo anti-inflammatory effect was examined by histologic and immunohistochemical analysis in TPA-induced mouse ear edema model. Results: The results of in vitro experiments showed that AAEO dose-dependently suppressed the release of pro-inflammatory mediators (NO, PGE2 and ROS) and cytokines (TNF-α, IL-6, IFN-β and MCP-1) in LPS-induced RAW264.7 macrophages. It down-regulated iNOS and COX-2 protein and mRNA expression but did not affect the activity of these two enzymes. AAEO significantly inhibited the phosphorylation of JAK2 and STAT1/3, but not the activation of MAPK and NF-κB cascades. In animal model, oral administration of AAEO significantly attenuated TPA-induced mouse ear edema and decreased the protein level of COX-2. Conclusion: AAEO suppresses inflammatory responses via down-regulation of the JAK/STATs signaling and ROS scavenging, which could contribute, at least in part, to the anti-inflammatory effect of AAEO. Graphical abstract: